Clinical and Radiologic Factors Associated With Detection of Mycobacterium tuberculosis in Children Under 5 Years old Using Invasive and Noninvasive Sample Collection Techniques—Kenya. (19th October 2022) - Smith, Jonathan P; Song, Rinn; McCarthy, Kimberly D; Mchembere, Walter; Click, Eleanor S; Cain, Kevin P
Abstract: Background: Pediatric tuberculosis (TB) remains a critical public health concern, yet bacteriologic confirmation of TB in children is challenging. Clinical, demographic, and radiological factors associated with a positive Mycobacterium tuberculosis specimen in young children (≤5 years) are poorly understood. Methods: We conducted a prospective cohort study of young children with presumptive TB and examined clinical, demographic, and radiologic factors associated with invasive and noninvasive specimen collection techniques (gastric aspirate, induced sputum, nasopharyngeal aspirate, stool, and string test); up to 2 samples were taken per child, per technique. We estimated associations between these factors and a positive specimen for each technique using generalized estimating equations (GEEs) and logistic regression. Results: A median (range) of 544 (507–566) samples were obtained for each specimen collection technique from 300 enrolled children; bacteriologic yield was low across all collection techniques (range, 1%–7% from Xpert MTB/RIF or culture), except for lymph node fine needle aspiration (29%) taken for children with cervical lymphadenopathy. Factors associated with positive M. tuberculosis samples across all techniques included prolonged lethargy (median [range] adjusted odds ratio [aOR], 8.1 [3.9–10.1]), history of exposure with a TB case (median [range] aOR, 6.1 [2.9–9.0]), immunologic evidence of M. tuberculosis infection (median [range] aOR, 4.6 [3.7–9.2]), large airway compression (median [range] aOR, 6.7 [4.7–9.5]), and hilar/mediastinal density (median [range] aOR, 2.9 [1.7–3.2]). Conclusions: Identifying factors that lead to a positive M. tuberculosis specimen in very young children can inform clinical management and increase the efficiency of diagnostic testing in children being assessed for TB. Abstract : We evaluated factors associated with positive Mycobacterium tuberculosis samples in children under 5 years old and found immunological evidence of M. tuberculosis infection, history of exposure with a tuberculosis patient, and prolonged lethargy were associated with a positive sample.